Nanocoatings size effect in nanostructured films - Aliofkhazraei, Mahmood (Engineering Materials., 2011)
ize effect in structures has been taken into consideration over the last years. In comparison with coatings with micrometer-ranged thickness, nanostructured coatings usually enjoy better and appropriate properties, such as strength and resistance. These coatings enjoy unique magnetic properties and are used with the aim of producing surfaces resistant against erosion, lubricant system, cutting tools, manufacturing hardened sporadic alloys, being resistant against oxidation and corrosion.   This book reviews researches on fabrication and classification of nanostructured coatings with focus on size effect in nanometric scale. Size effect on electrochemical, mechanical and physical properties of nanocoatings are presented.